Emotional Creativity and its relationship to Cognitive Representation and Locus of Control among Talented and Untalented High School female students in Makkah Al-Mukarramah - Alsubhi, Haneen Ibrahim (Journal of Educational and Psychological Sciences, 2023)
The current research aims to know the level of emotional Creativity, cognitive representation, to identify the type of control locus among talented and untalented students, to know the type of correlation between emotional Creativity, cognitive representation and control locus, and to detect differences in female students' grades in emotional Creativity, cognitive representation and control locus due to the different class of female students (talented, untalented), different grades (first, second, third), and different educational attainment grade. Averill's Emotive Creativity Scale (1999) translated by Munshar (2002), Zayat's Cognitive Representation Scale (1999), and Rotter's Locus of Control Scale (1966) Arabized by Kafafi (1982), the sample was selected in a random class manner, made up of 460 students, and the comparative link descriptive approach was used. The results showed a high level of Emotional Creativity for female students, average cognitive representation among female students, and the external control Locus was found to prevail among all female students. There was a statistically significant correlation between emotional Creativity and cognitive representation, the relationship between cognitive representation and the external control locus of untalented students was inverse, and a relationship between emotional creativity and internal control locus among talented students. There are statistically significant differences in the dimensions of emotional creativity, cognitive representation for talented female students, and statistically significant differences in the dimensions of cognitive representation of first-year High school students. There are statistically significant differences in the Emotional Creativity Scale, Cognitive Representation Scale, due to the different rate of academic attainment of the excellent rate. Upon these findings, recommendations have been reached, such as the preparation of training programs for High school students for the effective use of emotional creativity as an intermediary for cognitive representation, and programs to strengthen the internal control locus for students.
Keywords: Emotional Creativity; Cognitive Representation; Locus of Control; Talented; High school